Planejamento e avalia??o de inibidores alost?ricos para a super?xido dismutase de Leishmania braziliensis - Souza, Bruno Cruz de (2025)
Leishmaniasis is a neglected tropical disease (NTD) caused by protozoa of the genus Leishmania spp., responsible for about 30,000 annual deaths. Among its clinical forms, american cutaneous leishmaniasis (ACL) is a relevant public health problem in Brazil, with Leishmania braziliensis being its main etiological agent in the country. Despite its epidemiological impact, the pharmacological treatment for the disease is limited by the emergence of resistant strains, species-dependent efficacy and serious adverse effects. Within the biological targets in Leishmania spp., the enzyme iron superoxide dismutase (SOD) stands out due to its crucial role in the antioxidant pathway and in ensuring the parasite's survival, and its relevance is validated through genetic and chemical assays. The objective of this work was to obtain superoxide dismutase from Leishmania braziliensis (LbSOD) through cloning, expression and purification, while also prioritizing allosteric sites and inhibitors through computational methods. The activity of allosteric inhibitors for superoxide dismutase from Leishmania which were previously identified by computational techniques was evaluated against LbSOD through thermal displacement assays (ThermoFluor?). Additionally, the stability and interaction profile of the inhibitor-LbSOD complexes was evaluated using molecular dynamics routines, characterizing the interaction profiles of the complexes.